A Case of Exaggerated Pituitary Hyperplasia in a Pregnant Woman. Issue 1 (3rd February 2023) - Charitou, Marina M; Mathew, Ribu
Abstract: Pituitary hyperplasia occurs as a result of an increase in pituitary cell subtypes. It can be a consequence of either a physiological or pathological condition. In our case, a 31-year-old pregnant woman at 16 weeks gestation presented with headaches and vision changes. Visual field testing demonstrated bitemporal hemianopsia, and magnetic resonance imaging (MRI) brain showed enlargement of the pituitary with compression of the optic chiasm. She was treated with cabergoline and steroids, and her symptoms improved. In a subsequent pregnancy, the patient developed similar symptoms, and with cabergoline treatment, her symptoms resolved. A postpartum MRI of her brain revealed a decrease in pituitary size back to baseline with normal pituitary hormone levels. This patient's likely diagnosis was physiologic pituitary hyperplasia. Pituitary hyperplasia can be difficult to diagnose since there are no explicit guidelines. Through deduction of imaging findings and hormonal levels, diagnosis of pituitary hyperplasia becomes a more manageable task.